Dinosaurs. - Jackson, Kathryn, 1907-; Matternes, Jay H. ([Washington] National Geographic Society, 1972)
Pictures and brief text introduce the characteristics of various dinosaurs.
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs